Journey to Plum Creek - Cuate, Melodie A. (Book collections on Project MUSE., 2012)
""Hannah, Nick, and Jackie time-travel to Texas in 1840. Taken captive by Comanche warriors, Hannah and Jackie experience Comanche life and participate in the Linnville raid; Nick meets Bigfoot Wallace and the Texas Rangers, who pursue the Comanche party until the two groups clash in the Battle of Plum Creek"--